The impact of the marketing mix on the purchase decision of bread CV khasanah Sari in Subang - Rossy Anggilia; Andhi Sukma (Institute of Computer Science (IOCS), 2023)
The advancement in administration and goods makes every company develop its marketing system to follow the development of the organization. A showcase that deserves to be used as an attraction for advertisers is the Advertising Blend system, namely products, prices, areas, and promotions. Blend promotion is the core of an organization's marketing framework that must be able to influence interest in the products it produces. The motivation behind this study was to determine the Impact of Ad Mixes on Bread Buying Options in CV Khasanah Sari’s bread in Subang. This study uses quantitative methodology by utilizing important information obtained from the results of a poll circulated to 60 respondents of buyers CV Khasanah Sari’s in Subang. The information examination procedures used to answer exploratory speculation are legitimacy tests, dependency tests, old-style suspicion tests, and different straight relapse investigations. The results showed that value, area, and progress fundamentally influenced purchasing choices, whereas items did not at all influence purchasing choices for CVs. The fate of Sari Subang. Square's R value is 0.722 or 72.2%, and that implies that the Promotion Mix influences purchase choice, while the remaining 27.8% is influenced by other variables not in this review. As in this study that all independent variables simultaneously influence the decision to purchase CV bread. Khasanah Sari in Subang, therefore producers are expected to continuously increase their sales by paying attention to all variables.